Social Innovations in the Urban Context - Brandsen, Taco; Cattacin, Sandro; Evers, Adalbert; Zimmer, Annette (Nonprofit and Civil Society Studies, An International Multidisciplinary Series, 2016)
This book addresses the practice of social innovation, which is currently very much in the public eye. New ideas and approaches are needed to tackle the severe and wicked problems with which contemporary societies are struggling. Especially in times of economic crisis, social innovation is regarded as one of the crucial elements needed to move forward. Our knowledge of its dynamics has significantly progressed, thanks to an abundance of studies on social innovation both general and sector-specific. However, despite the valuable research conducted over the past years, the systematic analysis of social innovation is still contested and incomplete. The questions asked in the book are the following: 1. What is the nature of social innovations? 2.What patterns can be identified in social innovations emerging at the local level? 3.How is the emergence and spreadof social innovations related to urban governance? More precisely, which conditions and arrangements facilitate and hinders social innovation? We explore these questions using different types of data and methods, and studying different contexts. In particular, we focus on innovations that aim at solving problems of the young unemployed, single parents and migrants. The analysis is based on original research carried out in the period 2010-2014 in the framework of the European project WILCO.